Begin again - Luśnia, Monika Ewa (My University, 2021)
We stumble upon them, unpredictably, in certain life situations or during a side course of professional research. In both cases, with an unpleasant surprise. The blank spots on the map of groups represented by the built environment. Rehab care sector is one of them. It is often dealing with social stigma, to such extents, that even deliberate research leaves one with an impression, that there is very little straight-forward talk on the subject. The hope that an example of thoughtful and inclusive design for a rehab facility can contribute to changing this state of things and providing a more supportive built environment for the troubled members of the society, became the point of departure for this research. This work’s overall intention is to find solutions which will provide suitable rehab care, to those previously underserved. This includes rural communities and, among and beyond those, the patients with dual-diagnosis, women around pregnancy, underaged children of the patients and multiple cases of co-dependance. The research process involved gathering information from written sources, direct and indirect case studies, along attempts of getting in contact with authorities in the field, to retrieve practical information. The collected knowledge was first translated into a set of goals and strategies for the project and later on resulted with a design proposal, of a modular facility, which could be adapted to most given sites and have a potential for going from no infrastructure to a network of locally oriented facilities. The research investigation was limited to the extents of what proved to be useful in creating a general ‘know how’ for the design, leaving space for further iterations and clarifying the technical details. The generic elements were, however, designed in a way to never contradict the assumptions of sustainable design. At the moment of submitting this work, I can tell that it only touches the surface of what is a very broad and complex topic, but I do hope that it can help establishing a more open atmosphere for discussing issues connected to addiction treatment and the ways in which architecture can support addiction patients.
Keywords: female patient care, modular design, behavioral science; rehab facility, environmental psychology, non-definitive site, co-dependance